PALM BRICK AS A MEDIA FOR MALAY ART: AESTHETIC AND FUNCTIONAL DESIGN OF A BRIDAL GIVING PLACE - Solehat, Iis; Minawati, Rosta; Mulyadi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study explores the aesthetic and functional design of bridal gift containers crafted from woven palm fronds, emphasizing their potential to sustain and revitalize Malay cultural heritage. Malay art, rich in philosophical and symbolic meaning, serves as the foundation for this exploration, reflecting the life and traditions of the Malay community. Method: A Research and Development (R&D) approach was employed, beginning with cultural exploration through literature reviews and interviews to identify the values embedded in Malay art. Initial design concepts were developed via sketches and material experimentation. The prototypes were tested with users to evaluate their aesthetic and functional qualities, followed by iterative improvements based on feedback. Results: The study produced a bridal gift container that harmoniously integrates traditional Malay aesthetics with modern design innovations. This product not only enhances the wedding procession but also narrates the cultural richness of the Malay community, particularly in Mekar Sari Village, Maro Sebo Ulu District. Novelty: By utilizing palm fronds as a medium, this research bridges traditional craftsmanship and contemporary design, presenting a sustainable and culturally relevant art form that reinforces Malay identity in a modern context.